Anismus as a cause of functional constipation: Experience from Serbia - Jovanović Igor; Jovanović Dragana; Uglješić Milenko; Milinić Nikola; Cvetković Mirjana; Branković Marija; Nikolić Goran (Vojnosanitetski Pregled)
Backround/Aim. Anismus is paradoxal pressure increase or pressure decrease less than 20% of external anal sphincter during defecation straining. This study analyzed the presence of anismus as within a group of patients with the positive Rome III criteria for functional constipation. We used anorectal manometry as the determination method for anismus. Methods. We used anorectal waterperfused manometry in 60 patients with obstructive defecation defined by the Rome III criteria for functional constipation. We also analyzed anorectal function in 30 healthy subjects. Results. The presence of anismus is more frequent in the group of patients with obstructive defecation compared to the control group (a highly statistically significant difference, p < 0.01). Furthermore, we found that the Rome III criteria for functional constipation showed 90% accuracy in predicting obstructive defecation. We analyzed the correlation of anismus with the presence of weak external anal sphincter, rectal sensibility disorders, enlarged piles, diverticular disease and anatomic variations of colon. We found no correlation between them in any of these cases. Conclusion. There is a significant correlation between anismus and positive Rome III criteria for functional constipation. Anorectal manometry should be performed in all patients with the positive Rome III criteria for functional constipation.